The Homomorphism of Cubic bipolar ideals of a KU-semigroup - Awad, Wisam K.; Kareem, Fatema F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The idea of a homomorphism of a cubic set of a KU-semigroup is studied and the concept of the product between two cubic sets is defined. And then, a new cubic bipolar fuzzy set in this structure is discussed, and some important results are achieved. Also, the product of cubic subsets is discussed and some theorems are proved. 2010 AMS Classification: 06F35, 03G25, 08A72.